THE EFFECT OF CHATGPT IN FOSTERING SELF-DIRECTED LEARNING IN THE ESL WRITING CLASSROOM - Mohamad Yusop, Ewana (SEAMEO QITEP in Language, 2024)
This study investigates the effect of ChatGPT on students’ self-directed learning in the English Language writing classroom. With the increasing presence of AI tools in education, understanding its impact on students’ learning is essential. Grounded in Knowles’ (1975) Self-Directed Learning framework, this research explores the extent to which AI can support autonomy and self-assessment in student learning. The study is an quantitative exploratory study and employed a quasi-experimental design with an experimental group (N=24) using ChatGPT 3.5 for learning support and a control group without it (N=23). Quantitative data were gathered through pre- and post-surveys, measuring changes in students' self-assessment, motivation, study planning, and resource-seeking behaviors. Using paired-samples t-test, the quantitative analysis revealed that while ChatGPT significantly enhanced students' initiative and independence in learning in the experimental group, however other self-directed learning dimensions showed minimal impact. Additionally, the study’s results emphasizes that ChatGPT cannot replace the teacher's role, as it lacks the contextual understanding, instructional flexibility, and motivational influence critical for holistic student development. These insights highlight the need for educators to guide students in critically engaging with AI tools, using them to supplement rather than substitute the teacher's presence in the classroom.